Perception of students regarding sexual harassment - Dubey, Sarita; Verma, Tanima; Lata, Suman; Bharti, Trupti; Tavrej, Shams; Schan, Komal; Kashyap, Priyamvada; Gautam, Neelu (International Journal Of Community Medicine And Public Health, 2021)
Background: Sexual harassment means unwanted sexually determined behavior such as physical contacts and advances, making sexual derogative comments, and sexual pressure whether by verbal or -nonverbal actions. Young female adults are most vulnerable to harassment and violence towards them. Despite of high literacy levels young female adults show tendency to tolerate harassment and delay in early identification of warning signs, leading to sexual harassment. Therefore, it becomes very important to understand how the students perceive different types of sexual harassment. Objective of the study was to assess the perception of undergraduate girl students regarding Sexual Harassment. Methods: A descriptive, cross sectional survey design on 100 female undergraduate students from the King George’s Medical University of Lucknow, India was undertaken using convenient sampling technique. The data were collected from 15th May to 15th June 2018. A self structured perception questionnaire developed by researchers was used. Results: The data gathered from the study suggests that majority (81%) of the participants responded that sexual harassment is related to all unwelcome sexual behaviour, 72% of the participants feel most afraid of sexual harassment during night, and 83% of the participants responded that the most probable place for sexual harassment is public transport. 91% of the participants believed that the incidences of the sexual harassment has increased in the last 10 years and majority (81%) of the participants didn’t had knowledge of any legal provisions regarding sexual harassment. Conclusions: The data shows that the definition of sexual harassment can differ according to individual’s perception. To understand how people perceive and define sexual harassment is crucial for explaining and understanding how they react to sexual harassment and why they often do not stand up against sexual harassment.